1995
DOI: 10.1016/0014-5793(95)00088-q
|View full text |Cite
|
Sign up to set email alerts
|

GZ coupling to the rat κ‐opioid receptor

Abstract: We have expressed the cloned rat I¢-opioid receptor in human embryonic kidney 293 cells and studied the ability of K-selective ligands to inhibit adenylyl cyclase. In transfected 293 cells, activation of the ic-opioid receptor by U50,488 and the dynorphins resulted in the inhibition of cAMP accumulation. The inhibitory response was sensitive to pertussis toxin and highly selective for ic-agonists; neither /x-nor 6-opioids were able to activate the K-opioid receptor. Upon co-transfection with the subunit of Gz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 20 publications
(27 reference statements)
1
47
0
1
Order By: Relevance
“…Because the receptors of the opioid family are very similar in their pharmacology and specificity for coupling to G proteins, we investigated whether the DOR and the KOR would likewise be able to induce IP formation through Ga16. As we have previously established the amount of opioid receptor eDNA needed for analyzing receptormediated signal transductions in transient transfection systems (Lai et al, 1995;Tsu et al, 1995a), we examined the effect of transfecting COS-7 cells with DOR eDNA at 0.25 ,ug/ml in the absence or presence of varying amounts of Ga16 eDNA (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the receptors of the opioid family are very similar in their pharmacology and specificity for coupling to G proteins, we investigated whether the DOR and the KOR would likewise be able to induce IP formation through Ga16. As we have previously established the amount of opioid receptor eDNA needed for analyzing receptormediated signal transductions in transient transfection systems (Lai et al, 1995;Tsu et al, 1995a), we examined the effect of transfecting COS-7 cells with DOR eDNA at 0.25 ,ug/ml in the absence or presence of varying amounts of Ga16 eDNA (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because the MOR has been shown to interact with Ga16 (Offermanns and Simon, 1995), the present study examines the possible coupling of Ga16 to other subtypes (DOR and KOR) within the opioid receptor family. We have previously demonstrated that the ability of opioid receptors to interact with different G proteins can be conveniently assessed by transient transfection assays (Chan et a!., 1995;Lai et al, 1995;Tsu et al, 1995a). Thus, we monitored 16 coupling by cotransfecting COS-7 cells with cDNAs encoding Ga16 and an opioid receptor, followed by the determination of agonist-induced formation of inositol phosphates (IPs) in the transfected cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, introduction of GTP-␥-S into cells would activate the entire complement of HEK293 cell G-proteins (Zhou et al, 1995;Zong et al, 1995). Furthermore, we also used somatostatin receptors (Law et al, 1993;Shapiro and Hille, 1993;Reisine and Bell, 1995) and opioid receptors (Shen and Crain, 1994;Avidor-Reiss et al, 1995;Ikeda et al, 1995;Lai et al, 1995;Tallent et al, 1995), both of which can activate a wide variety of G-proteins. Interestingly, all of these manipulations produced robust inhibition of ␣ 1B channels, which had the same ancillary subunit composition as the ␣ 1E channels.…”
Section: Discussionmentioning
confidence: 99%
“…dopamine-D2, adenosine-A1, formyl peptide, complement C5a, and all three types of opioid receptors [8][9][10][11][12]. Although there is no indication of melatonin-mediated stimulation of adenylyl cyclase nor of possible coupling to PTX-insensitive G proteins, it is conceivable that the melatonin receptor may behave like the other G~-coupled receptors.…”
Section: Introductionmentioning
confidence: 99%